Preparation and Investigation of some Properties of Acrylic Resin Reinforced with Siwak Fiber Used for Denture Base Applications: Acrylic Resin, Natural fibers, Siwak, Denture. - Salih, Sihama I.; Oleiwi, Jawad K.; Fadhil, Hwazen S. (Kurdistan Journal of Applied Research, 2017)
Natural fibers have recently become attractive to researchers due to their low cost, fairly good mechanical properties, high specific strength, non-abrasive, eco-friendly, bio-degradability and biocompatibility characteristics, they are exploited as a replacement for the conventional fibers, such as glass, aramid and carbon. This study investigated the influence of fiber length and weight fraction of natural siwak fiber, with the selected length of (2, 6 and 12 mm) and weight fraction (3, 6 and 9 wt %), on some of mechanical and physical properties such as (tensile, impact and hardness), in addition to test the infrared spectroscopy FTIR of the prepared denture base resin and all of these tests were carried out at laboratory temperature.The properties of PMMA reinforced by natural fiber are mainly affected by the interfacial adhesion strength between the matrix and the fiber, and in order to improve interconnection between the siwak fiber and PMMA matrix, so the siwak fibers were treated with alkali (sodium hydroxide) solution prior to use as reinforcement materials. The results illustrated that the tensile strength, young modulus, fracture toughness and hardness tended to be improved with length and concentration ratios of siwak fiber, while the impact strength and elongation percentage at break decrease with fiber content in composite samples.